Refugees’ Crisis and European Union: a Mechanical Integrative Bargain - Charpentier, Loic (Global: Jurnal Politik Internasional, 2016)
This article describes the role of the refugees' crisis linked with the terrorist attacks of Paris on the European integration. This article is based on the Bartolini's theory to blur the boundaries between the international and internal system with the aim to explain the crisis mechanism of the European integration without being focused on the qualification of the European architecture. This article emphasizes the role of the external pressure on the particular political system of the European Union and their consequences concerning the integration process for the elites and for the European peoples. The refugees' example highlights the automatic integration process despite the lack of loyalty of the peoples to the European elites.